2021
DOI: 10.1136/bcr-2021-243764
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis induced or exacerbated by immune checkpoint inhibitors: a rising concern

Abstract: Immune checkpoint inhibitors can cause immune side effects, with myasthenia gravis (MG) being relatively rare. With this review, we present 66-year-old man with melanoma treated with pembrolizumab who developed MG. With immuno-oncology (IO) single agent usage, 42 cases reported new-onset MG and 9 cases reported exacerbation of pre-existing MG. Among the patients who had new-onset MG after administration of programmed cell death protein 1 (PD-1) inhibitors, 14 patients (38.8%) developed severe respiratory failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It's important to note that the presentation of de-novo MG has a more variable presentation than the standard MG. Recent literature has shown that de-novo MG correlates poorly with radiographic findings classically suggestive of MG such as thymoma or thymic hyperplasia [7,9]. Other studies have suggested that some phenotypes might even be subclinical in nature; thus, in the setting of acute illness, some subtypes of de-novo MG may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…It's important to note that the presentation of de-novo MG has a more variable presentation than the standard MG. Recent literature has shown that de-novo MG correlates poorly with radiographic findings classically suggestive of MG such as thymoma or thymic hyperplasia [7,9]. Other studies have suggested that some phenotypes might even be subclinical in nature; thus, in the setting of acute illness, some subtypes of de-novo MG may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, Immune checkpoint inhibitors (ICIs) are regarded as a therapeutic option for progressive malignancy even if autoimmune disorders such as myasthenia gravis (MG) are complicated in real-world settings. 1 Up to now, ICI-exacerbated preexisting bullous pemphigoid (BP) has been rarely reported unlike ICI-induced BP. 2 Therapeutic plasma exchange (TPE) is not mentioned for cutaneous immunerelated adverse events (IrAEs) on the American Society of Clinical Oncology clinical practice guidelines.…”
Section: Bullous Pemphigoid Exacerbated By Nivolumab and Temporally R...mentioning
confidence: 99%